The Impact of Carbon And Energy Prices on The Return of Energy Sector Stock in Selected Asia-Pacific Countires - Mawhibah Hasan Almas; Nora Amelda Rizal; Suhal Kusairi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The stock market is very important in the country's economy, namely as a source of corporate funding and especially in investments that have the aim of increasing the welfare of investors and companies. The purpose of this study is to analyze the effect of the rate of return on carbon costs, Brent crude oil, palm oil, interest rates, and exchange rates on the rate of return on energy stock prices in Asia-Pacific countries from 1st January 2016 to end of December 2021. In this study, the phenomena were explored utilizing quantitative approaches to collect data and test previously determined hypotheses. The panel data model is used, as well as the VECM (Vector Error Correlation Model) test. The results show that the influence of CO2 return on energy sector returns is negative in the short term but positive in the long term. Return on energy industry and return on Brent oil have both short-term and long-term unfavorable effects. The return of the use of palm oil has an advantageous long-term and short-term impact on the energy industry's return. The exchange rate has only a short-term negative relationship with the return of energy. Lastly, there is no long-term or short-term correlation between interest rates and the return on energy. The implication of this result is that industries must switch to using environmentally friendly devices and governments must declare regulations to emitters producers.